(untitled) (Fiep Bulletin - online, 2014)
This analytic essay presents the first reflections resulted from the teaching and research work developed in Radical Sports Subjects in the aquatic environment, from the teaching and bachelor’s degree curriculum of Physical Education in UFPEL. The analysis was done in the experience of administering the subject, and is focused on some emerging singularities of the inclusion of this non-conventional cultural practice in the university graduation curriculum, indicated by the teacher of the subject and authors of the essay, from the observations, photos, filming, and statements of the students. The first inference of the data we have available resulted in the elaboration of the subject program in which the analysis allows to indicate where the singularities of the surfing radical practices forced an introduction to new elements to the program. Following this, the authors bring out: the use of the Fluir Magazine as a source, in the same way that the existence of the academic bibliography about the subject is still rare; the non-linear elaboration of the script content for the subject; complicity and the corporal availability of students, the reason for the success of the subject in terms of accessed profit.